Simple time‐domain analysis of a multilevel DC–DC flying capacitor converter average aperiodic natural balancing dynamics. Issue 5 (4th March 2019) - Penczek, Adam; Mondzik, Andrzej; Stala, Robert; Ruderman, Alex
Abstract : Reported capacitor average natural voltage balancing dynamics analysis methods are mostly based on frequency‐domain Fourier transformations that involve infinite series. Therefore, these methods require high mathematical skills, are not truly analytical and difficult to use in engineering practise. This study suggests a time‐domain power averaging‐based approach to the analysis of a multilevel DC–DC flying capacitor converter (or, more generally, switched capacitive converter) aperiodic (non‐oscillating) average voltage balancing dynamics. Simple analytical solutions are illustrated by single and dual capacitor converter examples that include pure resistive load and balance booster circuit. Theoretical results are supported by simulations and experimental verification.